PENGARUH PENGHINDARAN PAJAK, BIAYA AGENSI, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Firmansyah Alfaina Fahyanzhuri Adlan (2021)
This study aims to determine the effect of tax avoidance, agency cost and dividend policies on the firm value in manufacturing companies listed on the Indonesia Stock Exchange in the period 2017-2019. This research is a type of quantitative research that uses secondary data in the form of the company's annual report. The study used a sample of 98 companies. The technique for analyzing the data in this study uses regression model selection test, classic assumption test, multiple linear regression, coefficient determination hypothesis test and partial hypothesis test (t test). The Fixed Effect Model (FEM) with panel data regression was used in this study using STATA version 16. Based on the results of the data analysis, it can be concluded that (1) tax avoidance has no influence on firm value, (2) Agency costs has no influence on firm value, (3) dividend policy has a significant positive influence on firm value, and variable control i.e. (4) leverage has a significant positive influence on firm value.